The Correlation between Students’ Vocabulary Mastery and Students’ Reading Comprehension - Netty Huzniati Andaz (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
Vocabulary is one of essential language element which help student to comprehend the reading text. Students are able to understand what they read easily if they have amount of vocabulary. Therefore, this research was aimed to explore the correlation of student’ vocabulary mastery and reading comprehension at the second Grade of SMPN 1 Kolaka. This research used quantitative descriptive design. The design of this research was quantitative descriptive. The population of this research was the second grade students of SMPN 1 Kolaka which was consisted of eight classes. The total number of the population was 206 students. To take the sample, the researcher used purposive sampling that was class VIIIB, it was comprised of 26 students. To gather the data, the researcher used two kinds of test; vocabulary test and reading test. The data was analyzed by using the formulation of Pearson Product Moment Correlation Coefficient. The result of data analysis showed that rxy was 0.705 was higher than rt was 0.404 with the degree of freedom (df=N-nr) was 24. Meanwhile, from the result of hypothesis testing was α ≠ 0 or rxy was higher than rt which meant the score of vocabulary and reading was straight comparable. So that, H0 and H2 was rejected and H1 was accepted. It was indicated that there was a positive correlation between students’ vocabulary mastery and students’ reading comprehension at the second grade of SMP Negeri 1 kolaka in academic year 2017/2018.